2006
DOI: 10.1111/j.1567-1364.2006.00062.x
|View full text |Cite
|
Sign up to set email alerts
|

The Na+,K+/H+-antiporter Nha1 influences the plasma membrane potential ofSaccharomyces cerevisiae

Abstract: There are three different sodium transport systems (Ena1-4p, Nha1p, Nhx1p) in Saccharomyces cerevisiae. The effect of their absence on the tolerance to alkali-metal cations and on the membrane potential was studied. All three sodium transporters were found to participate in the maintenance of Na+, Li+, K+ and Cs+ homeostasis. Measurements of the distribution of a fluorescent potentiometric probe (diS-C3(3) assay) in cell suspensions showed that the lack of all three transporters depolarizes the plasma membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 38 publications
6
52
0
Order By: Relevance
“…4), which can be indicative of suboptimal NAD ϩ levels and cofactor imbalance. Instead, high concentrations of Na ϩ , in the range of 0.5 to 1.0 M (Table 1), introduced during high-solid AHP pre- treatment and hydrolysis may have impaired xylose fermentation by inducing osmotic stress and impacting cell membrane potential, thereby limiting ATP production (76). Acetate is another well-known fermentation inhibitor that is commonly released from hemicellulose xylan under alkaline conditions (38).…”
Section: Discussionmentioning
confidence: 99%
“…4), which can be indicative of suboptimal NAD ϩ levels and cofactor imbalance. Instead, high concentrations of Na ϩ , in the range of 0.5 to 1.0 M (Table 1), introduced during high-solid AHP pre- treatment and hydrolysis may have impaired xylose fermentation by inducing osmotic stress and impacting cell membrane potential, thereby limiting ATP production (76). Acetate is another well-known fermentation inhibitor that is commonly released from hemicellulose xylan under alkaline conditions (38).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown previously that yeast lacking genes encoding Nhx1p displayed sensitivity to hygromycin B (36). The high sensitivity of nhx1⌬ cells to hygromycin B appears to be due to a defective sequestration of toxic cations into intracellular compartments (37), and the mechanism by which Nhx1p confers tolerance to hygromycin B appears to be associated with the role of Nhx1p in intravesicular pH regulation (16). vnx1⌬ cells also displayed sensitivity to hygromycin B, and the disruption of VNX1 in the nhx1⌬ strain resulted in the total growth inhibition of the double mutant nhx1⌬ vnx1⌬ cells.…”
Section: And LImentioning
confidence: 91%
“…Expression of enaA was upregulated approximately 31-fold in the ⌬cnaA cchA re strain after salt stress treatment compared with the non-salt-treated strain. However, the expression of two other sodium transporter genes, nhnA and trkA (50)(51)(52), showed no significant differences among the tested strains when treated with 800 mM NaCl. These results suggested that increased expression of enaA may bypass the requirement for calcineurin in the ⌬cnaA cchA re strain under salt stress.…”
Section: Figmentioning
confidence: 86%